mTOR signaling and endometrial receptivity in infertile women with intramural uterine leiomyomas - Annu Makker; Madhu Mati Goel; Dipti Nigam; Isha Makker; Amita Pandey (Middle East Fertility Society Journal, 2023)
Abstract Background Receptive endometrium is a restraining factor in the establishment of pregnancy in several estrogen-dependent gynecological disorders including uterine leiomyomas. Recently, data are beginning to accrue suggesting negative impact of non-cavity distorting intramural fibroids on molecular mediators of endometrial receptivity. The potential importance of the mammalian target of rapamycin (mTOR) signaling pathway has been suggested during embryo implantation. However, its exact role in fibroid-associated endometrium during the window of implantation is poorly defined. The objective of the study was to examine the expression and cellular distribution of key components of the mTOR signaling pathway during window of implantation in infertile women with non-cavity distorting intramural uterine leiomyomas (n = 24) as compared to fertile controls (n = 17). Relative gene expression analysis of mTOR, TSC1, and TSC2 was performed by real-time PCR. Immunohistochemistry was used to evaluate the expression of mTOR, phospho-mTOR (Serine 2448), TSC1, TSC2, phospho-TSC2 (Threonine 1462), and phospho-S6 ribosomal protein (Serines 235 and 236) and Ki67. Results In comparison to fertile controls, statistically significant upregulation of mTOR (8.97-fold; p < 0.001) and downregulation of TSC2 mRNA (− 6.01-fold; p < 0.01) levels and cell-specific upregulation of proteins phospho-mTOR, phospho-TSC2, and phospho-S6 and downregulation of TSC1 and TSC2 were observed in infertile women. The ratio of p-mTOR/mTOR and p-TSC2/TSC2 was significantly higher in infertile women. Pearson’s correlation analysis revealed significant negative correlation between p-mTOR and TSC2 and positive correlation between p-mTOR and p-S6 in the infertile group. Increased Ki67 labelling index was observed in the glandular epithelium (GE) and stroma of endometrium from infertile women as compared to controls. Conclusions Loss of TSC2 function and enhanced expression of activated mTOR and its downstream targets, observed in the infertile group, indicate heightened mTOR signaling which might contribute to impaired endometrial receptivity. Increased number of Ki67-positive nuclei suggests that enhanced mTOR signaling may help drive dysregulated proliferation of midsecretory endometrium leading to compromised fertility in women with non-cavity distorting intramural uterine leiomyomas. The present findings provide avenues for future investigation of mTOR pathway as a nonsurgical alternative for treatment of infertility in these patients.